Herbal Substance, Acteoside, Alleviates Intestinal Mucositis in Mice - Daniel Reinke; Stamatiki Kritas; Panagiotis Polychronopoulos; Alexios L. Skaltsounis; Nektarios Aligiannis; Cuong D. Tran (Gastroenterology Research and Practice)
This study investigated the role of acteoside in the amelioration of mucositis. C57BL/6 mice were gavaged daily with acteoside 600 μg for 5 d prior to induction of mucositis and throughout the experimental period. Mucositis was induced by methotrexate (MTX; 12.5 mg/kg; s.c.). Mice were culled on d 5 and d 11 after MTX. The duodenum, jejunum, and ileum were collected for myeloperoxidase (MPO) activity, metallothionein (MT) levels, and histology. Acteoside reduced histological severity scores by 75, 78, and 88% in the duodenum, jejunum, and ileum, respectively, compared to MTX-controls on d 5. Acteoside reduced crypt depth by 49, 51, and 33% and increased villus height by 19, 38, and 10% in the duodenum, jejunum, and ileum, respectively, compared to MTX-controls on d 5. Acteoside decreased MT by 50% compared to MTX-control mice on d 5. Acteoside decreased MPO by 60% and 30% in the duodenum and jejunum, respectively, compared to MTX-controls on d 5. Acteoside alleviated MTX-induced small intestinal mucositis possibly by preventing inflammation.